2012
DOI: 10.1021/la302676t
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Membrane Surface Charge by Trivalent Cations Probed with a Cation-Selective Channel

Abstract: We demonstrate that the cation-selective channel formed by gramicidin A can be used as a reliable sensor for studying the multivalent ion accumulation at the surfaces of charged lipid membranes and the “charge inversion” phenomenon. In asymmetrically charged membranes with the individual leaflets formed from pure negative and positive lipids bathed by 0.1 M CsCl solutions the channel exhibits current rectification which is comparable to that of a typical n/p semiconductor diode. We show that even at these high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
(129 reference statements)
3
32
0
Order By: Relevance
“…3B , the latter effect is greater. Positive charges on the membrane surface significantly decrease the rate of ion flux due to cation depletion near gA channels 32 34 . To compare the effects of different ILs, we analyzed the ion permeability rate as a function of IL concentration at a fixed time, i.e., 2 ms, after mixing liposomes with Tl + .…”
Section: Resultsmentioning
confidence: 99%
“…3B , the latter effect is greater. Positive charges on the membrane surface significantly decrease the rate of ion flux due to cation depletion near gA channels 32 34 . To compare the effects of different ILs, we analyzed the ion permeability rate as a function of IL concentration at a fixed time, i.e., 2 ms, after mixing liposomes with Tl + .…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know charge inversion has been reported in presence of salts of multivalent cations in systems of membrane channels [3][4][5], but only this is the first example concerning monovalent cations. Previous studies of charge inversion in systems in which the charge is pH-dependent mention specific adsorption of metal cations and correlation effects as potential candidates to explain charge inversion observations [10].…”
Section: Discussionmentioning
confidence: 92%
“…An extreme case occurs when interfacial charges attract counterions in excess of their own nominal charge, thus leading to an effective charge inversion of the system [1,2]. This phenomenon has been reported in diverse systems that are in contact with an aqueous solution containing multivalent ions: lipid vesicles, colloids, polyelectrolytes, Langmuir monolayers, membranes, nanopores and ion channels among others [1][2][3][4][5]. Here, we focus on the bacterial channel OmpF of E. coli [6] to report experimental evidence of charge inversion in presence of monovalent cations.…”
Section: Introductionmentioning
confidence: 99%
“…[408] An interesting approach to estimate the affinity of (multivalent) cations to membranes is to use channel proteins inserted into reconstituted lipid systems. Gurnev et al [409] employed a cation-selective channel to estimate the extent of charge inversion of lipid membranes of multivalent cations, revealing that La 3 + cations were more efficient at inverting membrane surface charge than hexaamminecobalt and spermidine. The effect of another trivalent cation was demonstrated by Ermakov et al [410] who showed a pronounced compaction of brain PS upon binding of Gd 3 + .…”
Section: Bilayers: Vesicles and Membranesmentioning
confidence: 99%